Effect of sulfonamidoethylenediamine substituents in RuII arene anticancer catalysts on transfer hydrogenation of coenzyme NAD+ by formate. Issue 21 (13th April 2018) - Chen, Feng; Soldevila-Barreda, Joan J.; Romero-Canelón, Isolda; Coverdale, James P. C.; Song, Ji-Inn; Clarkson, Guy J.; Kasparkova, Jana; Habtemariam, Abraha; Brabec, Viktor; Wolny, Juliusz A.; Schünemann, Volker; Sadler, Peter J.
Abstract : Organo-ruthenium complexes catalyse formate reduction of NAD +, and formate enhances their antiproliferative activity in cancer cells. Abstract : A series of neutral pseudo -octahedral Ru II sulfonamidoethylenediamine complexes [(η 6 - p -cym)Ru( N, N ′)Cl] where N, N ′ is N -(2-(R 1, R 2 -amino)ethyl)-4-toluenesulfonamide (TsEn(R 1, R 2 )) R 1, R 2 = Me, H (1 ); Me, Me (2 ); Et, H (3 ); benzyl, H (Bz, 4 ); 4-fluorobenzyl, H (4-F-Bz, 5 ) or naphthalen-2-ylmethyl, H (Naph, 6 ), were synthesised and characterised including the X-ray crystal structure of3 . These complexes catalyse the reduction of NAD + regioselectively to 1, 4-NADH by using formate as the hydride source. The catalytic efficiency depends markedly on the steric and electronic effects of the N -substitutent, with turnover frequencies (TOFs) increasing in the order:1 <2 <3, 6 <4, 5, achieving a TOF of 7.7 h −1 for4 with a 95% yield of 1, 4-NADH. The reduction rate was highest between pH* (deuterated solvent) 6 and 7.5 and improved with an increase in formate concentration (TOF of 18.8 h −1, 140 mM formate). The calculations suggested initial substitution of an aqua ligand by formate, followed by hydride transfer to Ru II and then to NAD +, and indicated specific interactions between the aqua complex and both NAD + and NADH, the former allowing a preorganisation involving interaction between the aqua ligand, formate anion and the pyridine ring of NAD + . The complexes exhibited antiproliferative activity towards A2780 human ovarian cancer cells with IC50 values ranging from 1 to 31 μM, the most potent complex, [(η 6 - p -cym)Ru(TsEn(Bz, H))Cl] (4, IC50 = 1.0 ± 0.1 μM), having a potency similar to the anticancer drug cisplatin. Co-administration with sodium formate (2 mM), increased the potency of all complexes towards A2780 cells by 20–36%, with the greatest effect seen for complex6 .